Realtà e verità in Jacques Ellul. Il dualismo parola-immagine - Coccimiglio, Cristina (Mechane, 2022)
In the same period in which Heidegger formulates his ontological proposal, Jacques Ellul – influenced by the judeo-christian conception of idolatry and by the philosophical conception of alienation in Marx – develops a systematic analysis of technology as a decisive social phenomenon in the modern world. Although the “philosophers” are a category criticized by Jacques Ellul, the sociological and theological reflection in his writings are recomposed in a dimension that reveals a complex and articulated vision of the world that can be explored with philosophical categories. The dualism of word and image represents a decisive key to interpreting the relationship between reality and truth.